United Nations and European Union in quest of Cyprus dispute solution - Makoveyenko, V.P. (Проблеми міжнародних відносин, 2012)
The objective of this article is to examine Cyprus dispute and assess contributions of the UN and the process of integration into the EU to its solution. This article provides brief historical overview of the dispute and highlights key political obstacles towards reaching an agreement. Particular attention is paid to the impact of European integration on the the settlement processes as well as Annan initiative. The author finds that there wouldn’t be a sustainable solution for Cyprus without support to the proposals from its Turkish-Cypriot and Greek-Cypriot communities. Мета статті полягає у дослідженні Кіпрського конфлікту та визначення внеску ООН та процесу євроінтеграції у його вирішення. У статті вивчаються головні історичні події конфлікту які зумовлюють політичні перепони його вирішення на сучасному етапі. Особливу увагу приділено впливу Європейської інтеграції на процес врегулювання конфлікту, а також ініціативи Плану Аннана. Автор доходить висновку, що без підтримки з боку турецько-кіпріотської та греко- кіпріотської громад неможливо досягти надійного вирішення Кіпрського конфлікту. Целью статьи является исследование Кипрского конфликта и оценки усилий ООН и ЕС, направленных на его решение. В статье определяются главные исторические события конфликта, которые препятствуют его решению. Особое внимание уделено влиянию процесса Европейской интеграции Кипра на решение конфликта, а также инициатива плана Аннана. Автор приходит к выводу, что невозможно достичь надежного решения конфликта без поддержки такого решения со стороны греко-киприотской и турко-киприотской общин.